2020
DOI: 10.3389/fnut.2020.578761
|View full text |Cite
|
Sign up to set email alerts
|

Korean Maize Hybrids Present Significant Diversity in Fatty Acid Composition: An Investigation to Identify PUFA-Rich Hybrids for a Healthy Diet

Abstract: Precise information on the content and composition of nutritionally essential metabolites in food crops is a prerequisite for dietary recommendations and nutrient-dense food formulations. In the present study, the fatty acid profile of 21 Korean maize hybrids was analyzed by gas chromatography (GC)-mass spectrometry (MS). In the studied hybrids, linoleic acid (LA; C18:2n6c) was dominant (38.0-58.9%), followed by oleic (OA; C18:1n9c) (23.5-45.3%), palmitic (C16:0) (10.8-17.3%), and stearic acids (C18:0) (1.84-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The findings presented by other researchers align with our results. Saini et al [ 45 ] found that linoleic acid was the dominant fatty acid in maize oil, with a content from 38% to 58.9%, while the amounts of oleic acid and palmitic acid were 23.5–45.3% and 10.8–17.30%, respectively [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings presented by other researchers align with our results. Saini et al [ 45 ] found that linoleic acid was the dominant fatty acid in maize oil, with a content from 38% to 58.9%, while the amounts of oleic acid and palmitic acid were 23.5–45.3% and 10.8–17.30%, respectively [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…The findings presented by other researchers align with our results. Saini et al [45] found that linoleic acid was the dominant fatty acid in maize oil, with a content from 38% to 58.9%, while the amounts of oleic acid and palmitic acid were 23.5-45.3% and 10.8-17.30%, respectively [45]. From a nutritional perspective, the emphasis extends beyond the content of individual polyunsaturated fatty acids to the crucial balance between n-6 and n-3 acids, each offering distinct health benefits.…”
Section: Groupmentioning
confidence: 99%
“…The crude lipids extracted from the spices and herb samples were used to prepare the FAMEs, following the previously optimized method [ 14 ] with minor modification. Briefly, 1 mL of a crude lipids sample was transferred into a 5 mL glass vial fitted with a Teflon-lined screw cap.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, canola oil (produced from low erucic-acid (<2%) cultivars of rapeseed) is mainly composed of oleic acid (54.0-61.0%), followed by LA (20.6-25.0%) and ALA (8.7-9.5%) with an n−6/n−3 PUFAs ratio of 1.9-2.5 [56]. Like soybean and palm oil, most vegetable oils contain a significant amount of MUFAs in the form of oleic acid (especially in olive, corn, safflower, and sunflower oil) [57], which impart good thermal and oxidative stability during storage and culinary preparations. Flax (linseed; Linum usitatissimum L., family Linaceae) seeds containing 35-50% oil [58] are a rich source of ALA (39.0 to 60.4% of total FAs) with low contents of SFAs (9-11%) [59,60].…”
Section: Ala-rich Seedsmentioning
confidence: 99%